A REVISION OF CYTISUS SECTIONS ALBURNOIDES, SPARTOPSIS AND VERZINUM (GENISTEAE, FABACEAE) - Auvray, G.; Malecot, V. (Edinburgh Journal of Botany, 2013)
Cytisus sections Alburnoides DC., Spartopsis Dumort. and Verzinum (Raf.) Talavera (tribe Genisteae, Fabaceae) are revised. These comprise 10 species of the genus, of which two species are recognised in Cytisus section Alburnoides, four in Cytisus section Spartopsis (of which two species are divided into subspecies), and four in Cytisus section Verzinum (one with two subspecies). Three new combinations are made: Cytisus ardoinoi subsp. sauzeanus, C. grandiflorus subsp. maurus and C. scoparius subsp. insularis. Keys to the sections and to the species within each section are given. All taxa are described. Conservation assessments are made.